Individual differences in cognitive performance and brain structure in typically developing children. (August 2015) - Yokota, Susumu; Takeuchi, Hikaru; Hashimoto, Teruo; Hashizume, Hiroshi; Asano, Kohei; Asano, Michiko; Sassa, Yuko; Taki, Yasuyuki; Kawashima, Ryuta
Highlights: We investigated the relationship between cognitive pattern and gray matter volume. Cognitive patterns were classified into 6 subtypes. Volume of right middle temporal gyrus was differentiated by cognitive patters. Abstract: Individual differences in cognitive patterning is informative in understanding one's cognitive strengths and weaknesses. However, little is known about the difference in brain structures relating to individual differences in cognitive patterning. In this study, we classified typically developing children ( n = 277; age range, 5–16 years) into subtypes with k-means cluster analysis along with factor index scores using the Wechsler Intelligence Scale for Children (Third Edition). We then applied voxel-based morphometry to investigate whether significant gray-matter-volume differences existed among subtypes of cognitive patterns. Depending on the level of performance and cognitive patterning, we obtained six subtypes. One subtype that generally scored below average showed larger volume in the right middle temporal gyrus than the other five. On the other hand, two subtypes that achieved average levels of performance showed reverse-patterned factor index scores (one scored higher in Verbal Comprehension and Freedom from Distractibility, and the other scored lower in these two factor index scores) and had smaller volume in the right middle temporal gyrus than the other subtypes. From these results, we concluded that cognitive discrepancy was also obvious in typically developing children and that differences in cognitive patterning are represented in brain structure.